Does Financial Liberalization Relax Financing Constraints on Firms? - Laeven, Luc (World Bank, Washington, DC, 2014)
The author uses panel data on 394 firms in 13 developing countries for the years 1988-98 to learn whether financial liberalization relaxes financing constraints on firms. He finds that liberalization affects small and large firms differently. Small firms are financially constrained before liberalization begins but become less so after liberalization. The financing constraints on large firms, however, are low both before and after liberalization. The initial difference between small and large firms disappears over time. The author hypothesizes that financial liberalization has little effect on the financing constraints of large firms because they have better access to preferential directed credit in the period before liberalization. Financial liberalization also reduces imperfections in financial markets, especially the asymmetric information costs of firms' financial leverage. Countries that liberalize their financial sectors tend to see dramatic improvements in political climate as well. Successful financial liberalization seems to require both the political will and the ability to stop the preferential treatment of well-connected, usually large, firms.